Expected Yield Stress and Tensile Strength Ratios for Determination of Expected Member Capacity in the 2005 AISC Seismic Provisions - Liu, Judy; Sabelli, Rafael; Brockenbrough, Roger L.; Fraser, Timothy P. (Engineering Journal, 2007)
In the 2005 AISC Seismic Provisions for Structural Steel Buildings, a factor, Rt, has been introduced for the ratio of expected tensile strength to the specified minimum tensile strength for use in calculating a modified strength for fracture limit states within designated yielding members. Additionally, for these provisions, some revisions have been made to the expected yield stress ratios, Ry, from the 2002 AISC Seismic Provisions for Structural Steel Buildings. These changes were based on a survey of recent mill certificates, as well as a review of published tensile property surveys.